Pengembangan Desa Sabuhur sebagai Desa Wisata Anggrek Lokal Kalimantan: Development of the Sabuhur Village as a Local Kalimantan Orchid Tourism Village - Istikowati, Wiwin Tyas; Sunardi, Sunardi; Abidin, Zainal; Surya, Adhi; Fauzan, Akhmad; Saputra, Debi Imam; Sari, Evita; Hidayanti, Nurul; Rizky, Akhmad Aufa; Rahmawati, Risma (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This community service activity aims to support environmental conservation activities carried out by the Forest Farmers Group (KTH) Amabilis Lestari and KTH Pantai Baru in Sabuhur Village, Jorong District, Tanah Laut, South Kalimantan. Partners are carrying out activities to save local Kalimantan orchids and ulin wood poles by searching for orchids and wooden poles around the Sabuhur village forest. The problem faced is that the orchids that are kept are moved to a new rearing location but their habitat does not match their natural habitat. In this activity, a smart greenhouse was built which used to maintain orchids, so that they resemble their natural habitat as closely as possible. An automatic watering system was created in the greenhouse, making it easier for partners to maintain orchids. Expansion of the orchid cultivation location was also carried out from the original area of only 2,500 m2 to 10,000 m2. Apart from that, partners have also started selling the orchids that they maintain. The improvement of partners’ skills also increased with this community service activity.